Load-balancing schemes for a hierarchical peer-to-peer file search system. (8th June 2011) - Cao, Qi; Fujita, Satoshi
In 2009, Qin et al. proposed a three-tier peer-to-peer (P2P) architecture for real-time file search in distributed networks. In this architecture, indices of files held by the user peers in the bottom layer are stored in the super-peers (SPs) in the middle layer, and the correlation of those two bottom layers is controlled by the central server(s) in the top layer using the notion of tags. In Qin et al.'s system, a heavily loaded SP can move excessive load to a lightly loaded SP by using the notion of task migration. However, such a task-migration approach is not sufficient to balance the load of SPs if the size of tasks is highly imbalanced. To overcome such an issue, in this paper, we propose two load-balancing schemes for this architecture, aiming to ensure an even load distribution over the SPs. The first scheme controls the load of each task in order to decrease the total cost of task migration. The second scheme directly balances the load over tasks by reordering the priority of tags used in the query-forwarding step. The effectiveness of the proposed schemes is evaluated by simulation. The result of the simulations indicates that all the schemes can work in coordination in alleviating the bottleneck situation of SPs.